Consumer attitudes towards online mobile advertising formats - Dias, Rogério Coimbra Henriques Lopes (2020)
Online advertising companies rely primarily on targeted advertising. It is a system that basically uses consumers data like search engine history, interests and demographic information to better understand what products or services consumers might want next, so to be able to optimize the advert. However, knowing what product the user wants next or what he or she finds interesting might not be enough. The way the ad is delivered is also relevant as mobile adverts can be deployed in many formats, like banner or video ads, and in many platforms, including mobile applications, search engines and mobile websites. The format in which mobile online adverts are deployed is often overlooked and left to companies or marketers to decide. We present a thorough analysis of existing ad formats and publishing platforms in which such formats can be presented. It is clear that some ad formats are more effective and more suitable for companies to use than others. The most effective ad formats out of the ones that have been analyzed are showcase shopping ads and product shopping ads presented on search engines, and carrousel ads on mobile applications. The rest of the ad formats were getting mixed reviews or very negative ones. Furthermore, it was found that users generally prefer to receive ads on the search engine publishing platform, and in certain ad formats the effectiveness can be distinguished through the use of the consumer’s demographic information on the receiving side.